METODE SUZUKI DALAM PEMBELAJARAN BIOLA DI SANGGAR MUSIK AMABILE - Kirana, Bunga Flamboyan; Ardini, Ni Wayan; Wiyati, Wahyu Sri (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
This observation aims to find out how important it is to apply the Suzuki method in violin classes at the amabile music studio, what advantages and obstacles I experienced during the learning process and what benefits students get from using the Suzuki method in the violin learning process. Apart from that, the author wants music teachers, especially violin, to know what and how the Suzuki method is used in the violin learning process. The Suzuki Method is an instrument teaching method created by Shinichi Suzuki. The Suzuki method prioritizes auditory training rather than reading a repertoire of songs. From the start of learning, students will not be taught to read first. From the observations it can be concluded that the Suzuki method is very important to use in the violin learning process at the Amabile Music Studio because this method has proven to be quite effective in helping students play the songs well and use the correct technique. Some of the benefits that students get when using the Suzuki method are good hearing training so that students can analysis notes better, good and correct body posture when playing the violin, and strong memory due to constant repetition. Some of the advantages of the Suzuki method itself are the training or learning which is quite detailed, the fingering patterns and the distribution of the bow are all regulated in the Suzuki method, the songs in the Suzuki book also sound familiar and enjoyable. There are three obstacles in using the Suzuki method, namely delays in the ability to read sheet music, minimal parental participation in the student's learning process at institutions and some students only memorize fingering patterns without knowing what notes are being played.